Decreased resting-state connections within the visuospatial attention-related network in advanced aging. (15th June 2015) - Li, Yujie; Li, Chunlin; Wu, Qiong; Xu, Zhihan; Kurata, Tomoko; Ohno, Seiichiro; Kanazawa, Susumu; Abe, Koji; Wu, Jinglong
Highlights: Elderly subjects responded to the target more slowly than young subjects did. Eleven ROIs were defined based on the activation map during the Posner task. Fifty-two of the 55 pairs of ROIs were positively correlated in the young group. Only 22 of the 55 pairs of ROIs were positively correlated in the elderly group. The SMA with the left AIC had reduced resting-state functional connectivity with age. Abstract: Advanced aging is accompanied by a decline in visuospatial attention. Previous neuroimaging and electrophysiological studies have demonstrated dysfunction in specific brain areas related to visuospatial attention. However, it is still unclear how the functional connectivity between brain regions causes the decline of visuospatial attention. Here, we combined task and rest functional magnetic resonance imaging (fMRI) to investigate the age-dependent alterations of resting-state functional connectivity within the task-related network. Twenty-three young subjects and nineteen elderly subjects participated in this study, and a modified Posner paradigm was used to define the region of interest (ROI). Our results showed that a marked reduction in the number of connections occurred with age, but this effect was not uniform throughout the brain: while there was a significant loss of communication in the anterior portion of the brain and between the anterior and posterior cerebral cortices, communication in the posterior portion of the brain was preserved. Moreover, the older adults exhibited weakened resting-state functional connectivity between the supplementary motor area and left anterior insular cortex. These findings suggest that, the disrupted functional connectivity of the brain network for visuospatial attention that occurs during normal aging may underlie the decline in cognitive performance.